Sequence analysis of a viral strain isolated for the first time in the UK, clarifies the identity of a novel species of fabavirus - Naomi Beddoe; Sam McGreig; Adrian Fox; Ian P. Adams; Alec Forsyth (Archives of Virology, 2026)
For the first time sequence data of a fabavirus was identified in dahlia from the UK, which was similar to virus sequence reported from dahlia in China. Initial sequences were determined by high-throughput sequencing (HTS) using the Illumina MiSeq platform, and were verified by Sanger sequencing and 5’ and 3’ rapid amplification of cDNA ends (RACE) polymerase chain reaction (PCR). The genome comprised two RNAs that were 5,851 nucleotide (nt) and 3,468 nt long, excluding the 3’-end poly-A tails, each RNA coded for a single polyprotein. The amino acid (aa) sequence identity percentages shared with recognised Fabavirus members over the protease-polymerase (Pro-Pol), Large Coat Protein (LCP) and combined Coat protein (CP) regions were in range with current demarcation thresholds for a distinct Secoviridae species. These sequence data analyses indicate that the fabavirus sequences identified in dahlia in both China and the UK represent a novel species in the family Secoviridae , genus Fabavirus . The name dahlia fabavirus (DFV) is proposed for this putative novel species tentatively named “ Fabavirus dahliae ”.